Organizations as power conflict sources - Lana, Raul Dalla; Paines, Patrícia Andrade; Bonaldo, Saul Azzolin; Müller, Felipe Martins (Revista de Administração da UFSM, 2016)
In this paper are presented a few power based organizations; the conflicts, power and conflict, power excercise and conflict resolution. Bibliographic research was used as this paper methodology, as it enables a rereading about the topic with a new perspective on writings from Bowditch, Foulcault, Galbraith, Mintzberg, Moscovici, Spector, and others. Literature points that the conflicts can be considered beneficial or malefic to the organization, as they can motivate an employee to grow, personally and professionally, possibilitating an better individual and group perforamnce. As to the resolution of this conflicts, the negotiation is an indicated alternative, as long as the professional in charge is capacitated, that is, he has the knowledge of the conflict generating process, to search for a solution that meets, in a reasonable and just way, the objectives, interests, needs and aspirations of the parts involved in the conflict. Therefore, the conflict can impose a threat to the organization stability as it can allow mutual growth, that is, the company, administrator and colaborator can get benefitted from a conflicting situation, as long as the correct alternatives are used for the conflict solving.